2005
DOI: 10.1152/ajpendo.00441.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic stress in diabetic pregnancy contributes to impaired embryo gene expression and defective development by inducing oxidative stress

Abstract: Before organogenesis, the avascular embryo is physiologically hypoxic (2-5% O2). Here we hypothesized that, because O2 delivery is limited at this stage of development, excess glucose metabolism could accelerate the rate of O2 consumption, thereby exacerbating the hypoxic state. Because hypoxia can increase mitochondrial superoxide production, excessive hypoxia may contribute to oxidative stress. To test this, we assayed O 2 flux, an indicator of O2 availability, in embryos of glucose-injected hyperglycemic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 54 publications
3
116
0
Order By: Relevance
“…Antimycin A is a mitochondrial complex III inhibitor that stimulates superoxide production [40,41] and mimics the effects of maternal diabetes on Pax3 expression and NTD [39,47]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antimycin A is a mitochondrial complex III inhibitor that stimulates superoxide production [40,41] and mimics the effects of maternal diabetes on Pax3 expression and NTD [39,47]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, congenital defects are still more frequent in infants of diabetic mothers than in the general population, in spite of adequate hyperglycaemia control in a large proportion of diabetic pregnant women. Recent reports have observed that the correlation between congenital malformations in infants of diabetic mothers and pre-pregnancy BMI is higher than that between congenital malformations and maternal blood glucose values [92], and that oxidative stress makes an important contribution to the increase in neural tube defects [93]. In addition, obesity and hyperinsulinaemia have been suggested as risk factors for neural tube defects in the general population [94].…”
Section: Relevance and Challenges Aheadmentioning
confidence: 99%
“…Thus, discordant expression of various genes may also result in NTDs by diabetes. However, only limited number of genes, such as Pax3 [7,11] and folate binding protein 1 (Folbp1) [12], has been analyzed in these models.…”
mentioning
confidence: 99%